Measuring Earnings Quality over Time - An, Yohan (International Journal of Economics and Financial Issues, 2017)
The purpose of this paper is to analyze earnings quality over the twelve years. We measure earnings quality as two types of dimensions: 1) decision usefulness and 2) stewardship (or accountability) based on the conceptual framework of the International Financial Reporting Standards (IFRS). This paper investigates earnings quality of listed firms on the Korean Stock Exchange (KSE) using a sample of 9,584 firm-year observations over the period 1995 to 2006. Earnings quality as decision usefulness is measured as persistence and value-relevance, while earnings quality as stewardship (or accountability is measured as conservatism and accruals quality. This study finds earnings quality of Korean firms is relatively lower than that of developed countries across three earnings quality dimensions except for conservatism. Thus, it is likely that Korean firms engage in earnings management in the presence of economic incentives, thereby reducing earnings quality. Keywords: Earnings Quality, Decision Usefulness, Stewardship JEL Classifications: G30, M4